Wik pedagogies: adapting oral culture processes for print-based learning contexts - Frazer, Baressa; Yunkaporta, Tyson (The Australian Journal of Indigenous Education, 2019)
Abstract This paper explores the possibilities of designing a Wik pedagogy, drawing on the language and culture of the remote community of Aurukun on Cape York. The research was inspired by the emergence of Aboriginal pedagogy theory in recent decades, along with a resurgence of interest in cognitive linguistics indicating an undeniable link between language, culture and cognition. We are Aboriginal researchers, relatives with strong family ties in the Aurukun community and beyond. We are bound by community obligations and cultural protocol and so the methodology privileged the local cultural and language orientations that inform Indigenous knowledge production. It involved participating in knowledge transmission in cultural contexts and undertaking a relationally responsive analysis of local language. The methodology enfolded Indigenous standpoint theory, yarning methods and auto-ethnography, a rigorous process that informed the development of a Wik pedagogy. We found that Wik knowledge transmission is embedded across multiple disciplines and modalities, such as weaving, fishing, carving, stories and images in both male and female cultural activities. The observed patterns of these activities revealed an example of a structured learning cycle. Some elements of this proposed Wik pedagogy may be generalisable to other language groups, such as the tendency for listening to be equated with understanding and cognition. This is a feature of many Aboriginal languages and cultures along with narrative, place-based and group-oriented approaches to knowledge transmission. In terms of implications for Indigenous research, the use of Indigenised methods such as umpan and relationally responsive analysis represent potential ways forward in Indigenous standpoint theory and methodologies.